Analyzing the Factors Affecting Google Search Engine Optimization for Iranian Academic Library Websites: One Comparative Study - Maryam Tavosi; Nader Naghshineh (Iranian Journal of Information Processing & Management, 2023)
Considering the growth of digital marketing, the present study was conducted by webometrics approach. In this study Iranian university library websites are analyzed from the standpoint of Google search engine optimization (SEO). Moreover, identifying the effective factors of Google SEO is done. The number of 30 effective components on Google SEO was obtained by using the agreement between two intelligent online SEO analysis tools ‘SEOsitecheckup’ and ‘SEOPtimer’, with a reliability coefficient of 0.77. The number of 17 components were identified with the help of texts and the library method (the numbers of 12 components were common in both methods). The research community consisted of 42 library websites of Iranian universities affiliated with the Ministry of Science, Research and Technology located in major cities of Iran. The data collection tools were the online analysis databases ‘SEOptimer’, ‘Ahrefs’, ‘Similarweb’, and ‘W3 Consortium’ (in addition to the checklist and identified components). The members of the community were analyzed from the standpoint of the 34 measurable components by SEO analysis tools (no need for the manager or administrator of the same website) on the cross-sectional study for six months at the beginning of the year 2020). ‘Excel’ and ‘LibreOffice Click’ software were used to analyze the data. None of the websites of Iran's university libraries got the final SEO score of 75 out of 100. Only thirty-three percent of Iranian university library websites had observed the ‘digital security certificate’ effective component on SEO. The websites of the central library of Sharif university of technology, and the digital library of Shahid Beheshti university were ranked respectively, from standpoint of the final Google SEO score. Connecting the website to various social networks such as LinkedIn, Facebook, and Instagram, is necessary to improve Google's SEO score, but it is not sufficient (only one effective component).The components affecting Google SEO can be divided into two groups. The first category can be adjusted by the administrators of the library website (including 29 components of the checklist offered in this present study and 1 component of the library website's compliance with the rules of the W3 consortium). The second category (including 4 components: ‘bounce rate’, ‘average visit duration’, ‘number of pages indexed in Google’, and ‘number of clicks or visits of uses) can be measured by the feedback of other websites or clicking of the users. Improving SEO-effective components along with having rich content will be valuable together with each other.